ANALISIS PROFIL KONSUMEN UNTUK PENGEMBANGAN APLIKASI FUTSAL MENGGUNAKAN PENDEKATAN DESAIN PROPOSISI NILAI - Setiawan, Rahmad; Sisilia, Kristina (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
This research will formulate consumer profiles of customer segments of futsal application products using the approach of value proposition design from Alexander Osterwalder and Yves Pigneur. The process of analysis is done by determining customer segments, identifying customer jobs, identifying customer pains, identifying customer gains, and drawing conclusions in the form of consumer profiles based on the results of customer identification Jobs, customer pains, and customer gains from the customer segment of futsal application. This research uses qualitative methods. Data collection is done with the triangulation technique. The validity test in this study uses the triangulation of the data validity technique. The data analysis techniques on this research use the theory of Miles and Hubberman in this regard by collecting data, reducing data, presenting data, and drawing conclusions. The result of the research is a consumer profile consisting of customer jobs, customer pains, and customer gains from the customer segment of the futsal application.Â Keyword: Customer Profile, Value Proposition Design, Futsal Application